The impact of reflective practice in a university language class. Issue 4 (4th July 2017) - Torres-Goens, Liliana; Farley, Lisa
Abstract: This study by a university professor of foreign language examines what impact reflective practice has on students' overall performance in a university language class. The findings support that reflective practice has a positive impact on students' performance and their own role in learning. The intertwining nature of reflection in all contexts of learning processes strengthens instructional practices which students favorably described throughout this study.